Improving Ecotourism and MSMES Competence Through Ecotravel and Local Business Boost in Puhu Payangan Village, Gianyar - DEWI, Anak Agung Istri Krisna Gangga; KURNIAWATI, Ni Putu Ayu Tika; PURNAMI, A.A Sri (Community Services: Sustainability Development, 2024)
This study aims to identify the potential challenges faced by Puhu Village, Payangan District, and Gianyar Regency in efforts to develop a tourism-based economy and empower MSMEs in the local village. Puhu Village is one of the villages in Bali that has abundant natural and cultural wealth, but has yet to be fully utilized. This study uses a qualitative approach with field observation methods, in-depth interviews, and secondary data analysis to collect relevant information. The study results indicate that Puhu Village has great potential in developing nature-based tourism sectors, such as agrotourism and ecotourism, supported by natural beauty, local wisdom, and local traditions. However, several challenges must be overcome, including a lack of supporting infrastructure, minimal promotion, and low community participation in tourism activities. This study recommends improving infrastructure, training for local communities, and more effective MSME promotion strategies to support economic development in Puhu Village. With proper management, the potential of this village can be developed sustainably and provide economic benefits to the local community without ignoring aspects of environmental and cultural preservation.